A Novel Electrochemical Sensor Based on Nanocomposite Film Electrode for Sensitive Determination of Environmental Hormone Bisphenol A - Li, Jun-Hua; Kuang, Dai-Zhi; Feng, Yong-Lan; Zhang, Fu-Xing; Liu, Meng-Qin (Asian Journal of Chemistry, 2013)
Bisphenol-A (BPA) is an emerging contaminant with severe toxic effects such as disrupting endocrine system or causing cancer, therefore, developing sensitive and selective sensor for bisphenol-A is very important and interesting. Herein, mesoporous hydroxyapatite (meso-HAP) and mesoporous titanium dioxide (meso-TiO2) have been synthesized and an electrochemical sensor for bisphenol-A was fabricated based on immobilizing meso-hydroxyapatite, meso-TiO2 and multi-walled carbon nanotubes (MWCNT) onto glassy carbon electrode (GCE) surface. Compared with bare electrode and single layer modified electrode, meso-HAP/meso-TiO2/ MWCNT modified electrode not only significantly enhanced the oxidation peak current of bisphenol-A, but also lowered the oxidation overpotential, suggesting that the prepared sensor can remarkably improve the determining sensitivity of bisphenol-A. Factors influencing the detection processes were optimized and the kinetic parameters were also investigated. Under the optimized conditions, the oxidation peak current was proportional to bisphenol-A concentration in the range from 8.0 × 10-9-4.0 × 10-7 M with the correlation coefficient of 0.9979. The detection limit was 1.0 × 10-9 M (S/N = 3). The fabricated electrode showed good reproducibility, stability and antiinterference. The proposed method was successfully applied to determine bisphenol-A in plastic products and the results were satisfactory.